2018
DOI: 10.12973/iejme/3966
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Mathematical Problem Solving Ability and Self-Efficacy through Guided Discovery Learning in Local Culture Context

Abstract: Qualified learning materials is needed in the efforts to improve the quality of teaching-learning mathematics. Qualified learning materials can be obtained through development research. Learning materials in this study were learning materials that were developed based on guided discovery learning model. The learning materials was also developed by integrating local culture into a guided learning model. The local culture in this study was adapted to the local culture of the students, namely the Batak Toba. Lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
39

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 24 publications
7
170
0
39
Order By: Relevance
“…Besides, the psychoanalytic ontology of desire puts stress on another ambivalence. The very situation of being of the I am possible only if the Other opposes in the final satisfaction of this desire, that is, the situation of desire turns out to be impossible for the subject [13][14][15][16][17][18]. The I am destined to experience the permanent loss of the object of desire, alienation from the Other [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the psychoanalytic ontology of desire puts stress on another ambivalence. The very situation of being of the I am possible only if the Other opposes in the final satisfaction of this desire, that is, the situation of desire turns out to be impossible for the subject [13][14][15][16][17][18]. The I am destined to experience the permanent loss of the object of desire, alienation from the Other [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…The very situation of being of the I am possible only if the Other opposes in the final satisfaction of this desire, that is, the situation of desire turns out to be impossible for the subject [13][14][15][16][17][18]. The I am destined to experience the permanent loss of the object of desire, alienation from the Other [14][15][16][17]. Despite this, it is only thanks to this constant loss of the object of desire and the impossibility of fully satisfying the desire that the I become viable to fight for its being and gaining the fullness of being.…”
Section: Resultsmentioning
confidence: 99%
“…Their research showed that the mathematical understanding of students taught using learning-based context was higher than those taught using the conventional method. Furthermore, Simamora, et al (2018) and Ulandari, et al (2019) used Batak context to improve students' mathematical problem solving abilities and self-efficacy. Simamora integrated the context in their learning strategy.…”
Section: Researcher (R)mentioning
confidence: 99%
“…In this context, the post-traumatic condition often turns out to be the mechanism of social consolidation and differentiation ("grief united"). The ability to recognize the "community of pain" serves as a social watershed, symbolically isolating the "survivors" from everyone else" [13,18].…”
Section: International Journal Of Engineering and Advanced Technologymentioning
confidence: 99%